2013
DOI: 10.1177/0310057x1304100509
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Learning for the ANZCA Final Examination and Validation of the Revised Study Process Questionnaire in Specialist Medical Training

Abstract: When evaluating assessments, the impact on learning is often overlooked. Approaches to learning can be deep, surface and strategic. To provide insights into exam quality, we investigated the learning approaches taken by trainees preparing for the Australian and New Zealand College of Anaesthetists (ANZCA) Final Exam. The revised two-factor Study Process Questionnaire (R-SPQ-2F) was modified and validated for this context and was administered to ANZCA advanced trainees. Additional questions were asked about per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
3
10
1
Order By: Relevance
“…We attempted to address this bias through using researchers with no involvement in the anaesthesia training program to conduct the interviews and undertake the primary analysis. The small number of interviewees in a qualitative study limits generalisability of findings, but our numbers were consistent with usual sample sizes in qualitative research and the data is consistent with findings in a previous study including 236 survey respondents 19 .…”
Section: Limitationssupporting
confidence: 88%
See 2 more Smart Citations
“…We attempted to address this bias through using researchers with no involvement in the anaesthesia training program to conduct the interviews and undertake the primary analysis. The small number of interviewees in a qualitative study limits generalisability of findings, but our numbers were consistent with usual sample sizes in qualitative research and the data is consistent with findings in a previous study including 236 survey respondents 19 .…”
Section: Limitationssupporting
confidence: 88%
“…In a previous study 19 , we surveyed anaesthesia trainees on their approaches to learning for the ANZCA Final Examination. Respondents used both deep and surface approaches, with a clear preponderance of deep approaches.…”
Section: Impact Of Anzca Examinations On Learning and Wellbeingmentioning
confidence: 99%
See 1 more Smart Citation
“…36 In contrast to our results (Figure 3), Sullivan et al described a higher deep to surface approach to learning ratio of 1.49 for 46 finalyear UK medical students, 37 while Weller et al found an even higher ratio of 1.87 in 236 medical trainees preparing for the Australian and New Zealand College of Anaesthetists final exam. 38 Our study had some limitations, the most evident of which is the short observation period. Indeed, it appears that one year is not long enough to see the full benefits of a faculty development program in teaching and learning skills development.…”
Section: Discussionmentioning
confidence: 91%
“…34 38 Our study had some limitations, the most evident of which is the short observation period. Pandey and Zimitat found a 0.97 proportion in first-year medical students studying anatomy at an Australian university.…”
Section: Discussionmentioning
confidence: 94%